(untitled) (Fiep Bulletin - online, 2015)
the nursing is a historicamente feminine profession, in its primórdios the cares to the patients was effected by religious women, widowers and or noblemen, with the objective to carry through charity. In the year of 1854, a noble English lady of name Florence Nightingale, that served in the war of the Criméia as voluntary in the English military hospitals, in full field of war, iníciou the professionalization of the nursing. Currently the nursing is subdivided in categories: nurse, technician of nursing and assistant of enfermagem.O Technician of military Nursing, receives the one overload from physical and intense work, beyond the specific functions the nursing has other military responsibilities and activities, causing bigger physical consuming and estresse. This study he had for objective to verify the morfofuncionais characteristics of military Technician of Nursing, of the feminine sex of a located military hospital in the City of Rio De Janeiro. They had been chosen because they are they responsible them for the well-taken care of right-handers to the patients. For the evaluation of the obesidade level index of corporal mass was used (IMC), for the probability of cardiológico risk the RCQ and for evaluation of the cardiorespiratória aptitude the Test of Race of 12 Cooper minutes was used (1968). After the evaluation of the data we can conclude that in this group, the military of the 40-49 band years are best the conditional ones.